2018
DOI: 10.1155/2018/3016304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molybdenum on the Corrosion Behavior of High‐Entropy Alloys CoCrFeNi2 and CoCrFeNi2Mo0.25 under Sodium Chloride Aqueous Conditions

Abstract: The corrosion behavior of high-entropy alloys (HEAs) CoCrFeNi2 and CoCrFeNi2Mo0.25 was investigated in 3.5 wt. percent sodium chloride (NaCl) at 25°C by electrochemical methods. Their corrosion parameters were compared to those of HASTELLOY® C-276 (UNS N10276) and stainless steel 316L (UNS 31600) to assess the suitability of HEAs for potential industrial applications in NaCl simulating seawater type environments. The corrosion rates were calculated using corrosion current determined from electrochemical experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…In current usage, HEAs are multicomponent alloys with generally few solid solution phases of simple structure (such as body-centered cubic (BCC), face-centered cubic (FCC), or hexagonal close packed (HCP)) [14][15][16][17]. HEAs have been reported to have unusual properties of many types (including corrosion, mechanical, thermal and electrical properties, and wear properties [15][16][17][18][19][20][21][22][23]), and these behaviours suggest the potential for use in numerous applications, including nuclear, aerospace, energy, chemical, electronics, and marine infrastructure [15,17,24,25]. In particular, several HEA systems have been reported to show improved corrosion properties.…”
Section: Introductionmentioning
confidence: 99%
“…In current usage, HEAs are multicomponent alloys with generally few solid solution phases of simple structure (such as body-centered cubic (BCC), face-centered cubic (FCC), or hexagonal close packed (HCP)) [14][15][16][17]. HEAs have been reported to have unusual properties of many types (including corrosion, mechanical, thermal and electrical properties, and wear properties [15][16][17][18][19][20][21][22][23]), and these behaviours suggest the potential for use in numerous applications, including nuclear, aerospace, energy, chemical, electronics, and marine infrastructure [15,17,24,25]. In particular, several HEA systems have been reported to show improved corrosion properties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a relatively low intensity Mo 3d spectra was recorded because of the oxidation states of the Mo 3d region overlap, the curve fitting becomes complicated to achieve the spectra owing to the almost similar energy levels of Mo 3d 3/2 and Mo 3d 5/2 . The signal intensity of Mo 4+ (228.40 eV, 231.40 eV) increased, which indicated that the prepassivation enhanced the enrichment of Mo and further made the passive film much denser (Kraack et al, 1995;Rodriguez et al, 2018). The addition of Mo into stainless steel has a significant effect on promoting the enrichment of Cr in the passive film and thus prolonged the induction period in Cl − concentrated environment (Sugimoto and Sawada, 1977;Li et al, 2017).…”
Section: The Xps Analysismentioning
confidence: 99%
“…I corr is determined in the linear part of the polarization curve by deducting Tafel extrapolation, where the polarization resistance (R p ) is calculated according to formula (6). Therefore, I corr is the most important index for evaluating the corrosion resistance of WE [34][35][36]. According to table 6, as x increases I corr gradually increases, indicating that Cu reduces the corrosion resistance of Al 0.8 CrFeCoNiCu x HEAs.…”
Section: Wear Testmentioning
confidence: 99%